Carbon dots synthesized at room temperature and application of carbon dots in detection of H2O2
By synthesizing iron-doped carbon dots at room temperature, the problems of high energy consumption and high cost in traditional carbon dot synthesis methods are solved, and direct and fast H2O2 detection is achieved using its fluorescence characteristics, which has the advantages of low energy consumption, low cost and high sensitivity.
Patent Information
- Application Number
- CN202510079361.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-17
AI Technical Summary
In the prior art, the carbon dot synthesis method has problems such as high energy consumption, high cost, complex operation and many side reactions, and there are fewer methods to directly detect H2O2 using the fluorescence characteristics of the carbon dots.
Iron-doped carbon dots were prepared by oxidation, cross-linking polymerization and Schiff base reaction at room temperature and normal pressure, using hydroquinone and orthophenyldiamine as carbon sources, and trivalent iron as reaction catalysts and doping elements, low-energy synthesis of carbon dots was achieved, and H2O2 was directly detected using its fluorescence characteristics.
It realizes low energy consumption and low cost synthesis of carbon dots, with the advantages of simple operation, simple equipment, high output and adjustable process. It also realizes direct, fast and sensitive H2O2 detection through the fluorescence quenching of H2O2, with the detection limit as low as 0.028 µmol/L.
Smart Images

Figure CN119823756A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material preparation and analysis and detection, and specifically relates to fluorescent carbon dots prepared at room temperature, and using the carbon dots for H2O2 detection. Background Art
[0002] Hydrogen peroxide (H2O2) is widely used as a bleaching agent, disinfectant, preservative, etc. due to its strong antioxidant properties and easy decomposition. It is widely used in environmental protection, papermaking, textiles, food and medical fields. H2O2 is also involved in regulating cell growth, differentiation, apoptosis and other processes in animals and plants. Excessive H2O2 can induce human gene mutations and cause cancer; H2O2 can also decompose and generate hydroxyl free radicals in the human body, leading to the destruction of cell structure and causing cardiovascular and diabetes diseases. In 2017, the World Health Organization's International Agency for Research on Cancer identified H2O2 as a carcinogen, so accurate and efficient detection of H2O2 is of great significance. At present, the commonly used H2O2 detection methods include electrochemical method, fluorescence method, surface enhanced Raman scattering method, colorimetry, etc. Among them, the fluorescence method has attracted much attention because it not only has good selectivity and high sensitivity, but also has the advantages of simple operation and low cost. Although there have been many reports on the use of organic small molecule fluorescent probes to detect H2O2 (ACS sensors, 2020, 6(1):54-62; Analytical chemistry, 2021, 93(6):3301-3307), their synthesis is difficult and cannot be easily mastered by some laboratories without a deep organic synthesis background. Therefore, it is extremely challenging to develop fluorescent materials with simple synthesis methods and excellent performance to achieve simple and rapid H2O2 detection.
[0003] As a powerful photoluminescent nanomaterial, carbon dots (CDs) are widely used in optoelectronics, bioimaging, fluorescence sensing, medical treatment and catalysis due to their low toxicity, excellent optical behavior, excellent chemical stability, high photostability and good biocompatibility. So far, carbon dots can be prepared by hydrothermal method, solvothermal method, microwave method, electrochemical exfoliation and other methods. Although these methods can prepare many carbon dots with excellent performance, they have the disadvantages of high energy consumption and certain dangerous operation. For example, the most commonly used hydrothermal synthesis method usually requires 150 ~ 230 ○C under high temperature and high pressure, which may lead to safety risks; other preparation methods have cumbersome operations and many side reactions, and some equipment is complex and expensive, especially when prepared under high energy consumption, resulting in high cost and low efficiency. In addition, these methods are usually carried out in a sealed environment, making it difficult to monitor and control the reaction process. It is worth noting that although there are reports on the use of carbon dots as probes for H2O2 detection, most of them use the enzyme-mimicking activity of carbon dots, and enzyme substrates need to be added for detection (Sensors and Actuators B: Chemical, 2019, 287: 408-415; Journal of Alloys and Compounds, 2021, 862: 158323; ACS Applied Nano Materials, 2024, 7(15): 17795-17803), while there are few reports on the direct detection of H2O2 using the fluorescence properties of carbon dots. Summary of the invention
[0004] In view of the shortcomings of the carbon dot synthesis method in the background technology, the present invention provides a carbon dot prepared at room temperature and normal pressure and its application in H2O2 detection. At room temperature, hydroquinone and o-phenylenediamine are used as carbon sources, trivalent iron is used as a reaction catalyst and doping element, and long-wavelength emitting iron-doped carbon dots are prepared by catalytic oxidation, cross-linking polymerization and Schiff base reaction. Doping metal elements in carbon dots is an effective method to improve the performance of carbon dots, and as a low-energy consumption method, room temperature synthesis of carbon dots has the characteristics of simple equipment, low energy consumption, high output, adjustable process and low cost, which meets the needs of energy-saving chemistry and solves the shortcomings of high energy consumption and high cost in traditional carbon dot preparation methods. In addition, H2O2 can directly quench the fluorescence of the carbon dots prepared by the present invention, and H2O2 detection can be performed without adding additional reagents, which has the advantages of simplicity, rapidity, high sensitivity and good selectivity.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: In a first aspect of the present invention, a room temperature synthesis method of carbon dots is provided, the synthesis method comprising the following steps: adding hydroquinone, o-phenylenediamine, iron salt, and ultrapure water into a beaker, forming a transparent uniform solution under ultrasonic treatment, placing the solution on a magnetic stirrer for stirring and reacting at room temperature and pressure to obtain a brown suspension; centrifuging the obtained suspension, filtering the supernatant with a 0.22 µm filter membrane, and then dialyzing and freeze-drying the solution to obtain the carbon dots.
[0006] Preferably, the mass ratio of hydroquinone to o-phenylenediamine is 1:1 to 1:3, the amount of iron salt is 0.01 to 0.05 g, the amount of ultrapure water is 10 to 20 mL, the reaction temperature is room temperature, and the reaction time is 18 to 24 h; Preferably, the iron salt is ferric nitrate; Preferably, the centrifugal treatment speed is 8000 r / min and the time is 5 to 15 min.
[0007] The second aspect of the present invention provides carbon dots prepared by the preparation method described in the above technical solution, characterized in that the carbon dots have a spherical structure, the particle size of the carbon dots is about 8 nm, and they have excellent fluorescence properties.
[0008] The third aspect of the present invention provides the application of the carbon dots described in the above technical solution in H2O2 detection.
[0009] Preferably, the application includes: 1) Add carbon dots to buffer to prepare a detection solution, add H2O2 solution of different concentrations, measure the fluorescence intensity of the resulting mixed solution before and after the reaction, and establish a H2O2 standard curve based on the relationship between H2O2 concentration and fluorescence intensity change value; 2) Adding the sample to be tested into the carbon dot detection solution, measuring the fluorescence intensity of the obtained mixed solution before and after the reaction, substituting it into the H2O2 standard curve, and calculating the H2O2 content in the sample to be tested.
[0010] Preferably, a citric acid-sodium citrate buffer system is used, the pH of the detection system is 6, and the H2O2 concentration in the H2O2 solution to be detected is ≥ 0.028 µmol / L.
[0011] The technical solution provided by the present invention has the following beneficial effects: 1. The carbon dots provided by the present invention can be prepared at room temperature, the prepared carbon dots have uniform size, good stability and resistance to photobleaching, and also have the advantages of low energy consumption, low cost, green environmental protection, simple operation, easy availability of raw materials, and easy large-scale preparation; 2. H2O2 has a significant fluorescence quenching effect on the carbon dots prepared by the present invention, and the degree of quenching is related to the concentration of H2O2. Direct quantitative detection of H2O2 can be achieved without the introduction of other auxiliary reagents. It has the advantages of simple operation, good selectivity and high sensitivity, and the detection limit is as low as 0.028 µmol / L. 3. The detection method provided by the present invention is applied to the detection of H2O2 in actual water samples and foods, and exhibits good reproducibility, reliability and accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 The transmission electron microscope image and particle size distribution diagram of carbon dots prepared in Example 1 of the present invention; Figure 2 This is the UV-visible absorption spectrum of the carbon dots prepared in Example 1 of the present invention; Figure 3 This is the infrared absorption spectrum of carbon dots obtained in Example 1 of the present invention; Figure 4 This is a high-resolution X-ray photoelectron spectrum of carbon dots obtained in Example 1 of the present invention; Figure 5 The fluorescence excitation and emission spectra of carbon dots prepared in Example 1 of the present invention are shown; Figure 6 The fluorescence emission spectra of the carbon dots prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention are shown; Figure 7 The fluorescence emission spectra of the carbon dots prepared in Example 1 of the present invention in the presence of different concentrations of H2O2; Figure 8 This is a linear relationship diagram between the fluorescence intensity of the carbon dots obtained in Example 1 of the present invention and the H2O2 concentration; Fig. 9 This is a diagram showing the selectivity experimental test results of carbon dots prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0013] In order to explain the content of the present invention more clearly and in depth, some embodiments are further listed below, but the present invention is not limited to the listed embodiments. If the specific experimental conditions or methods in the following examples are not specified, they are carried out according to the conventional conditions or methods in the art. Example 1
[0014] Accurately weigh 0.035 g of hydroquinone, 0.10 g of o-phenylenediamine, and 0.030 g of ferric nitrate, add 10 mL of ultrapure water, and form a transparent uniform solution under ultrasonic treatment. Then, after stirring and reacting at room temperature for 18 h, a brown suspension is obtained. The obtained product is centrifuged at 8000 r / min for 10 min to remove the precipitate, and the supernatant is filtered with a 0.22 µm filter membrane, dialyzed, and freeze-dried to obtain carbon dots.
[0015] The carbon dots obtained in Example 1 were analyzed by transmission electron microscopy. Figure 1 As shown. Figure 1 It can be seen that the prepared carbon dots have a spherical structure and good dispersibility, with an average particle size of 8.0±0.1 nm.
[0016] The carbon dots obtained in Example 1 were tested by UV-visible spectroscopy. Figure 2It can be seen that carbon dots have two absorption peaks at 250 nm and 430 nm, which are respectively generated by the π→π* transition and n→π* transition of the chemical bonds in the carbon dots.
[0017] The carbon dots obtained in Example 1 were analyzed by infrared spectroscopy. Figure 3 As shown, 3430 cm -1 It is caused by the stretching vibration of OH / NH. The stretching vibration of CH appears at 1622 cm -1 1512 cm -1 The absorption peak at 1460 cm is caused by the stretching vibration of C=N / C=C. -1 1389 cm -1 The absorption peak at 1225 cm is caused by the stretching vibration of -NO2. -1 The absorption peak at 1092 cm is caused by the stretching vibration of NH, and the stretching vibration absorption peak of CO appears at 1092 cm -1 The Fe-O stretching vibration absorption peak appears at 570 cm -1 , these absorption bands indicate the formation of multi-ring structures and the successful doping of Fe.
[0018] X-ray photoelectron spectroscopy analysis was performed on the carbon dots obtained in Example 1 to further study the chemical composition of the prepared carbon dots, indicating that the carbon dots had four peaks of C 1s, N 1s, O 1s and Fe 2p, located at about 284 eV, 399 eV, 532 eV and 741 eV, with relative element contents of 67.86%, 14.21%, 17.1% and 0.83%, respectively; Figure 4 A shows the four fitting peaks of the high-resolution C1s spectrum of carbon dots: C=C / CC (284.4 eV), CN (285.1 eV), C-OH (286.0 eV) and C=N / CO (288.0 eV); Figure 4 B shows the three fitting peaks of the high-resolution N 1s spectrum of carbon dots: CN=C (399.1 eV), -NH2 (400.6 eV) and -NO2 (406.5 eV); Figure 4 C shows two fitting peaks of the high-resolution O 1s spectrum of carbon dots: C=O (531.7 eV) and COC / C-OH (532.5 eV); Figure 4 D shows two fitting peaks of the high-resolution Fe 2p spectrum of carbon dots: Fe 2p 3 / 2 , (711.8 eV) and Fe 2p 1 / 2 (726.2 eV), indicating the successful doping of Fe ions.
[0019] The carbon dots obtained in Example 1 were subjected to fluorescence spectrum analysis, and the test results were as follows: Figure 5 .Depend on Figure 5 It can be seen that as the excitation wavelength increases, the emission wavelength of carbon dots remains unchanged, and its fluorescence intensity first increases and then decreases. Its optimal excitation wavelength is 390 nm, and the maximum emission wavelength is 553 nm.
[0020] The carbon dots obtained in Example 1 were continuously irradiated with ultraviolet light. After irradiation for 0, 5, 10, 20, 30, and 40 min, the fluorescence intensities of the fluorescent carbon dots were 1619, 1617, 1600, 1602, 1592, and 1586, respectively. It can be seen from the above measurement results that after long-term irradiation, the fluorescence intensity of the carbon dots remained basically unchanged, indicating that the obtained carbon dots have good resistance to photobleaching.
[0021] NaCl solutions of different concentrations were mixed with the carbon dots obtained in Example 1, and the mixed solution was subjected to fluorescence detection. When the salt ion concentration varied between 10 mM and 500 mM, the fluorescence intensity and the fluorescence emission peak position of the carbon dots did not change significantly, which indicates that the obtained carbon dots can maintain good chemical and optical stability even at higher ionic strength. Example 2
[0022] Carbon dots were prepared in the same manner as in Example 1, except that the amount of ferric nitrate added was 0.010 g. Example 3
[0023] Carbon dots were prepared in the same manner as in Example 1, except that the amount of ferric nitrate added was 0.050 g.
[0024] Comparative Example 1 Carbon dots were prepared in the same manner as in Example 1, except that the amount of ferric nitrate added was 0.
[0025] Fluorescence detection was performed on the carbon dots obtained in Example 1, Example 2, Example 3 and Comparative Example 1. The detection results are as follows: Figure 6 As shown, when the amount of ferric nitrate was 0 mg, 0.010 mg, 0.030 mg, and 0.050 mg, the fluorescence intensity was 1185, 1680, 1601, and 1324, respectively. When ferric nitrate was not added during the preparation process, the fluorescence of the obtained carbon dots was weak. With the increase of the amount of ferric nitrate added, the fluorescence of the obtained carbon dots first increased and then decreased. The fluorescence intensity of the carbon dots synthesized under the conditions of the embodiment of the present invention was better. Example 4
[0026] The carbon dots obtained in Example 1 were subjected to H2O2 detection, and the operation steps were as follows: 100 mL (1 mg / L) of carbon dot solution and 100 mL of H2O2 (100 mmol / L) were added to a 1.5 mL centrifuge tube, and then 800 mL of citric acid-sodium citrate buffer solution (pH=6, 0.1 M) was added, mixed evenly, and allowed to react for 5 min, and fluorescence detection was performed at room temperature. During the fluorescence detection process, the slit width of the excitation light was set to 5 nm, the slit width of the emission light was 5 nm, the voltage of the photomultiplier tube detector was 700 v, the maximum excitation wavelength was 390 nm, and the maximum emission wavelength was 553 nm. △F represents the difference in the change in fluorescence intensity of the system after adding H2O2.
[0027] Comparative Example 2 The carbon dots obtained in Example 2, Example 3 and Comparative Example 1 were subjected to H2O2 detection, and the operation steps were the same as those in Example 4.
[0028] The fluorescence intensity change △F before and after adding H2O2 in Example 4 and Comparative Example 2 was calculated. It was found that when the carbon dots obtained in Comparative Example 1, the carbon dots obtained in Example 2, the carbon dots obtained in Example 1, and the carbon dots obtained in Example 3 were used, after adding 100 mL H2O2 (100 mmol / L), the △F values of the systems were 106, 301, 346 and 185, respectively, indicating that the carbon dots obtained in Example 1 had the best quenching effect on H2O2.
[0029] Comparative Example 3 The H2O2 detection was carried out according to Example 4, except that the pH of the buffer solution in the detection system was 3, 4, 5, and 7, respectively.
[0030] The change value △F of fluorescence intensity before and after adding H2O2 in Example 4 and Comparative Example 2 was recorded. The △F values were 30 (pH=3), 134 (pH=4), 213 (pH=5), 352 (pH=6), and 128 (pH=7), respectively, indicating that the quenching effect of H2O2 was best when a buffer solution with a pH of 6 was used.
[0031] Comparative Example 4 H2O2 detection was performed according to Example 4, except that the buffer solution systems in the detection system were: acetate buffer system, phosphate buffer system and Tris-HCl buffer system, respectively. The fluorescence intensity change value ΔF before and after adding H2O2 in Example 4 and Comparative Example 4 was calculated, and the ΔF values were 286 (acetate buffer system), 25 (phosphate buffer system), 349 (citrate buffer system), and 13 (Tris-HCl buffer system), respectively, indicating that the citrate buffer system has the best quenching effect on H2O2. Example 5
[0032] According to the operation steps of Example 4, a series of H2O2 standard solutions with different concentrations were added to the detection system consisting of the carbon dots obtained in Example 1 and the citric acid-sodium citrate buffer solution with pH 6, and the fluorescence changes were recorded. Figure 7 As shown in the figure, when the concentration of added H2O2 is between 1 µmol / L and 500 µmol / L, the fluorescence intensity of the obtained fluorescence emission spectrum curve gradually decreases as the concentration of H2O2 increases. Figure 8 Reason Figure 7 The linear relationship between the obtained △F value and H2O2 concentration is fitted, and its linear equation is △F = 25.28+ 2.491 c (µmol / L), correlation coefficient R 2 =0.9967, and the detection limit was 0.028µmol / L (S / N=3). Example 6
[0033] In order to investigate the selectivity and anti-interference of the carbon dots obtained in Example 1 in the H2O2 detection process, common metal ions and organic matter were added to the detection system and the corresponding fluorescence responses were recorded (Na2O2 and Na2O2 at the same concentration were added). + , K + , Cu 2+ , Mn 2+ , Pb 2+ , Ca 2+ Mg 2+ 、Zn 2+ , Fe 3+ , glucose, fructose, humic acid, glycine, malic acid), the blank control is the fluorescence intensity when no H2O2 is added (i.e., only carbon dots). The results of fluorescence response are shown in Fig. 9 shown by Fig. 9 It can be seen that Na + , K + , Mn 2+ , Pb 2+ , Ca 2+ Mg 2+ 、Zn 2+ , Fe 3+ , glucose, fructose, sucrose, humic acid, glycine, and malic acid had little effect on the fluorescence intensity of the system, while Cu 2+ It has a great influence on the determination of H2O2, but adding EDTA can mask Cu 2+ The results show that the carbon dots obtained by the present invention have good selectivity for H2O2 and are not affected by other interferences.
[0034] Application Example 1 In order to verify the practical application performance of the fluorescent carbon dots obtained in the present invention in H2O2 detection, tap water and pickled pepper chicken feet were tested respectively, and a spiked recovery test was carried out. The recovery rates were 97.5% ~ 103.8%. The results are shown in Table 1, indicating that the experimental method provides a wide linear detection range and a low detection limit, is suitable for on-site and rapid analysis and detection, and has great development prospects.
[0035] Table 1 Recovery test of the carbon dots obtained in the present invention for H2O2 in water samples and foods (n=3).
[0036]
[0037] It can be seen from the above embodiments that the present invention uses hydroquinone and o-phenylenediamine as starting materials, adopts a simple room temperature stirring method, and synthesizes fluorescent carbon dots with excellent fluorescence properties by adding a certain amount of iron salt. H2O2 can significantly quench the fluorescence of the prepared carbon dots, thereby realizing direct fluorescence detection of H2O2 with high sensitivity and a detection limit as low as 0.028µmol / L; and the carbon dots prepared at room temperature by the present invention not only have good anti-photobleaching properties and stability, but also have mild reaction conditions, no need for high temperature and high pressure, safe operation, and can achieve low-cost large-scale synthesis.
[0038] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A carbon dot synthesized at room temperature, characterized in that: The preparation is carried out through the following steps: at room temperature, hydroquinone, o-phenylenediamine, iron salt and ultrapure water are mixed, ultrasonically treated to form a uniform solution, and then placed on a magnetic stirrer for stirring to obtain a brown suspension; the suspension is centrifuged, and the obtained supernatant is filtered, dialyzed, and freeze-dried to obtain carbon dots.
2. The method for preparing carbon dots according to claim 1, characterized in that: The mass ratio of hydroquinone to o-phenylenediamine is 1:1 to 1:3, the amount of iron salt is 0.01 to 0.05 mg, the amount of ultrapure water is 10 to 20 mL, the reaction temperature is room temperature, and the reaction time is 18 to 24 hours.
3. The method for preparing carbon dots according to any one of claims 1 to 2, characterized in that: The iron salt is one or a combination of two or more of ferric nitrate, ferric sulfate, ferric chloride and ferric acetate.
4. The method for preparing carbon dots according to any one of claims 1 to 2, characterized in that: The centrifugal speed is 8000 ~10000 r / min and the time is 5 ~ 15 min.
5. The method for preparing carbon dots according to any one of claims 1 to 2, characterized in that: The filtration was performed using a 0.22 µm filter membrane, the molecular weight cut-off for the dialysis was 500, and the dialysis time was 12 to 24 h.
6. A carbon dot synthesized at room temperature, characterized in that: The carbon dots are prepared by the preparation method according to any one of claims 1 to 5, and have a spherical structure, a particle size of about 8 nm, and excellent fluorescence properties.
7. The use of carbon dots in detecting H2O2 according to claim 6, characterized in that: The following steps are involved: 1) adding the carbon dots described in claim 6 to a buffer solution to prepare a detection solution, adding H2O2 solutions of different concentrations, measuring the fluorescence intensity of the resulting mixed solution before and after the reaction, and establishing a H2O2 standard curve based on the relationship between the H2O2 concentration and the fluorescence intensity change value; 2) Adding the sample to be tested into the carbon dot detection solution, measuring the fluorescence intensity of the obtained mixed solution before and after the reaction, substituting it into the H2O2 standard curve, and calculating the H2O2 content in the sample to be tested.
8. The use of carbon dots in detecting H2O2 according to claim 7, characterized in that: The buffer used was citric acid-sodium citrate buffer solution at pH 6.0; The mixed solution was allowed to stand for 5 to 10 min before fluorescence detection.
Citation Information
Patent Citations
One-step preparation method for white light-emitting carbon dots
CN108929682A
Iron-doped carbon dots as well as preparation method and application thereof
CN113736457A
Fluorescent carbon dot and test paper capable of detecting Hg < 2 + > based on smart phone
CN114994002A
Iron-doped carbon dots as well as preparation method and application thereof
CN117987143A
Red fluorescent carbon dots as well as preparation method and application thereof
CN118772876A